STRATEGI KOMUNIKASI DAN PEMASARAN EFEKTIF DALAM PENGEMBANGAN DESA WISATA MIRAT - Kunkun Kurniawan; Reiza D Dienaputra; Awaludin Nugraha (Jurnal Pariwisata Pesona, 2021)
Unique and authentic landscapes attract tourists. Hanging Rock and Camping Ground Arya Kemuning and Sanghyang Dora are natural tourist attractions owned by Mirat Village. As a new tourist destination in Majalengka Regency, the tourism stakeholders of Mirat village play an important role in developing the existing tourism potential to increase the number of tourist visits. This study aims to determine the marketing communication strategy carried out by the village government and Kelompok Sadar Wisata (POKDARWIS), the factors that support and hinder the marketing communication strategy in increasing tourist visits to the Mirat tourism village. This study uses a phenomenological method with a qualitative approach. The data source used is primary with data collection techniques through observation, interviews, and documentation. The results showed that the marketing communication strategy carried out by the village government and Kelompok Sadar Wisata (POKDARWIS) had a positive impact on increasing the number of tourists. The success of the marketing communication strategy is supported by the unique appeal of tourist destinations in Mirat Village. Although there are obstacles in terms of accessibility and amenities, it is hoped that in the future there will be the right solution through alternative shuttle bus transportation to tourist locations and improving the quality of amenities to support tourist comfort.